Light‐Induced Nonoxidative Coupling of Methane Using Stable Solid Solutions. (11th August 2021) - Wang, Guangming; Mu, Xiaowei; Li, Jiayang; Zhan, Qingyun; Qian, Yumeng; Mu, Xiaoyue; Li, Lu
Abstract: Achieving efficient and direct conversion of methane under mild conditions is of great significance for innovations in the chemical industry. However, the efficiency and lifetime of most catalysts remain too far from practical requirements, since it is difficult to break the first C−H bond of methane as well as to suppress the following complete dehydrogenation (or overoxidation) and the resulting carbonaceous deposition (or CO2 ). Here, we report that wurtzite GaN:ZnO solid solutions exhibit unique and unprecedented photocatalytic performances for the nonoxidative coupling of methane at room temperature, exclusively generating ethane with nearly stoichiometric H2 . High conversion rate (>330 μmol g −1  h −1 ), long‐term stability (>70 h), and superior coke‐resistance were achieved. At 293 K, the methane conversion exceeds 7 %, comparable to the equilibrium conversion of thermal catalysis at 910 K. Mechanistic studies revealed that the N‐ZnGa ‐ON units and the absence of acid sites on the surface played crucial roles in reactivity and coke resistance, respectively. Abstract : An efficient and robust light‐driven nonoxidative coupling of methane (NOCM) to ethane and hydrogen at room temperature was developed. The noble‐metal‐free GaN:ZnO solid solution drove NOCM with a high conversion rate, high selectivity, long‐term stability, and superior coke resistance, which are difficult to achieve simultaneously in thermal catalysis.